National Dam Inspection Program (NDI ID Number PA-00893, DER ID Number 66-35), Winola Mill Pond Dam, Susquehanna River Basin, Tributary to Beaver Creek, Wyoming County, Pennsylvania. Phase I Inspection Report - Futchko,Frederick (1979)
Based on visual inspection, available records, calculations and past operational performance, and according to criteria established for these studies, Winola Mill Pond Dam is judged to be unsafe, nonemergency, because the spillway capacity is rated as seriously inadequate. The existing walls of the main spillway will overtop at about 6 percent of the Probable Maximum Flood(PMF). Overtopping of the walls will cause erosion of the dry masonry section of the dam. It is estimated that the 15 percent PMF would cause sufficient erosion to cause the dam to fail. The initial surge from the failure of the dam would increase the hazard to loss of life downstream. As a whole, the dam is judged to be in fair condition. Cracks have developed in the concrete liner wall on the upstream face of the dry masonry. Excessive leakage and a hole in the upstream earthfill had previously developed and the repairs made to the structure do not eliminate the possibility of these conditions reoccurring. Although a preliminary stability analysis indicates no apparent need for immediate concern, the theoretical stability of Winola Mill Pond Dam is unknown because the foundation conditions are unknown. Original contains color plates: All DTIC and NTIS reproductions will be in black and white.